Pemeriksaan Visus pada Anak Sekolah Dasar Sebagai Upaya Menjaga Mata Pasca Pandemi Covid-19 - Zuhroh, Diah Fauzia; Anggrassari, Anggun Pranessia (Idea Pengabdian Masyarakat, 2023)
Eyes are one of the five senses that are useful for getting various kinds of information. While at school, this function plays an important role considering that the teaching and learning process is accepted through the five senses. This is in contrast to the current situation where the pandemic prevents children from attending school face to face. The intensity of learning through gadget media makes parents worried because children will tend to spend more and longer time with these devices so that it can have an impact on children's eye health. Early detection and periodic examination of children's eyes can reduce these problems considering the eye is one of the vital functions of the body. Through visual inspection using the Snellen Chart card, it can detect the function of visual acuity in children. This Community Service Program uses an outreach method at the beginning of the activity by educating students about the importance of maintaining eye health, followed by taking turns checking vision. The target in this program is 102 students accompanied by assistance from teachers and school health workers. Based on the results of the examination, some students (59%) had normal vision and they were very enthusiastic when the education was given. Thus, periodic visual inspection in the school environment is very important to facilitate the learning process in children.